ANALISIS KUALITAS PELAYANAN TERHADAP JASA ANGKUTAN DARAT ANTAR NEGARA PADA PERUM DAMRI (Rute Pontianak-Khucing) - B11107139, Evivianus Ivo (Jurnal Manajemen Update, 2013)
Public enterprise (PERUM DAMRI) Station of Pontianak is a company which concern in the field of transportation.it is seek a profit by way of utilizing the people needs of transportation services. So it created a profit both of sides. In this business, services becomes very important thing. It is because the more consumers feel satisfied,the more loyal them. This research was foccused to know what kind of market method that is used by DAMRI Station Pontianak from route Pontianak-Kuching. It also includes the measurement of variables dimention such as Tangiable, Realiability, Responsiveness, Assurance, Empathy, in relation with the incrasing of selling volume. This research using a survey method, which is taking the sample from population that is use a questionnaire as main tool of data collecting. The saple taken using purposive sampling technique, a method that makes the researcherdeliberaty choose the sample based on certain criteria which have been set before. The sampe consist of 100 respondens, and also consist of single person that have been used the transportation services at PERUM DAMRI Station of Pontianak route Pontianak-Kuching. The method of analysis that used is importance performance analysis, and cartesius diagram analysis, that was taken from the data that has been collected, and also the questions were answered by the respondents in the questionnaire. Then those answers were tabulated and presented in tables form as well asin the analysis in accordance with the research objectives through percentage. The result of this research indicate that the service which already given by PERUM DAMRI Pontinak was good enough. It seen from the 5 dimensions of service quality measurement such as: the Tangiable is 1 in quadran A at point 2, 2 in quadran B at points 1 and 4, and 1 in quadran c at point 3. From Realibility 1 indicator in quadran A at point 7, 1 in quadran B at point 8,and 2 in quadran C at points number 6 and 9,also 1 in quadran D at point 5. From Responsiveness 2 in quadran A at points 10 and 11, 1 in quadran B at point 12, and 1 in quadran C at point 13. From Assurance 2 in quadran B at points number 15 and 16, and 2 in quadran D at poin 14 and 17. From Empathy aspect 1 in quadran A at poin number 20 1 in quadran B yaitu at point number 18, 1 in quadran C at point number 22, and 2 in quadran D at points 19 and 21.